DETERMINANTS OF FINANCIAL PERFORMANCE BASED ON LOCAL ORIGINAL REVENUE (PAD), BALANCING FUNDS, CAPITAL EXPENDITURE, AND BUDGET CALCULATION SURFER (SILPA - Rizkita, Divanda Oktavia; Suhartini, Dwi (JURNAL AKUNTANSI FINANCIAL STIE SULTAN AGUNG, 2025)
Local governments must continue to manage their finances better as part of the implementation of decentralization that was established in 1999, especially in stabilizing revenue realization due to the impact of the pandemic. Based on DJPK data, the financial efficiency ratio of provincial local governments in Indonesia shows that the majority of provinces are in the inefficient category in the 2020-2023 average calculation. According to several previous researchers, financial performance can be influenced by Local Own-Source Revenue (PAD), Balance Funds, Capital Expenditure, and Budget Surplus (SiLPA). Therefore, the purpose of this study is to examine the extent to which PAD, Balance Funds, Capital Expenditures, and Budget Surplus (SiLPA) affect financial performance at the provincial government level through efficiency ratios. The novelty of this study is that it combines these four variables into a comprehensive analysis model of regional financial performance using quantitative methods with multiple linear regression analysis. This study took secondary data from the official website of the Directorate General of Fiscal Balance with a population of all provincial governments in Indonesia. Amount of 136 samples were selected through purposive sampling in this study. The results show that PAD and SiLPA have no effect on the financial performance of provincial governments. On the other hand, Fiscal Balance Funds have an effect.